Football intelligence. Training and tactics for soccer success - Teoldo, I.; Guilherme, J.; Garganta, J. (Routledge, 2022)
Soccer is the biggest game in the world and has proved to be an unprecedented phenomenon of social impact, inhabiting a prominent place in the daily lives of millions of human beings, a game that has impact even in the most remote places. In an ever-changing world of soccer coaching and tactics, player intelligence has become increasingly important, providing the essential ability to act effectively in a given moment. Therefore, in recent years, the tactical component has been increasingly valued and diffused. Around the world, this dimension of sport performance is being studied and applied by many professionals in the field, from the youth academies all the way through to the professional level.